PERGESERAN OTORITAS SOSIAL DAN KULTURAL GURU: ANALISIS SOSIO-ANTROPOLOGIS KONFLIK PENDIDIK DAN ORANG TUA DALAM KASUS PENDISIPLINAN SISWA DI JAMBI - Hamzah Irfanda; Yana Alfita Dea Nova; Suci Herdayanti; Juriya Adhandini; Fajri Afrialdi (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study examines shifts in teachers' social and cultural authority through a socio-anthropological analysis of conflicts between educators and parents regarding student discipline in Jambi. The study is motivated by the increasing criminalization of teachers stemming from disciplinary actions at school that escalate into legal and social issues, a trend exacerbated by digital media's role in accelerating public judgment. A qualitative approach was employed, utilizing case study methods within a constructivist paradigm. Primary data were obtained through content analysis of the viral video "Teacher Suspected of Conducting Hair Raid on Students in Jambi," while secondary data were drawn from legal documents, media reports, academic journals, and literature on the sociology and anthropology of education. Digital ethnography was applied to analyze public narratives and responses in digital spaces. The findings reveal that the conflict originated from the enforcement of hair regulations as part of the teacher's pedagogical responsibilities; however, due to post-Reform shifts in social values and growing individual rights awareness, parents interpreted these actions differently. The failure of communication and mediation caused the conflict to escalate from the school environment to formal legal proceedings, ultimately reaching a hearing before the House of Representatives' Commission III. Social media functioned as an "informal court" that preceded formal legal processes and accelerated public judgment before facts were fully verified. This study concludes that the issue is structural and socio-anthropological in nature, necessitating stronger legal protections for teachers, greater clarity regarding disciplinary boundaries, and improved communication and mediation mechanisms between schools and parents.